Increased glutamate + glutamine levels in the thalamus of patients with essential tremor: A preliminary proton MR spectroscopic study. (February 2018) - Barbagallo, Gaetano; Arabia, Gennarina; Novellino, Fabiana; Nisticò, Rita; Salsone, Maria; Morelli, Maurizio; Rocca, Federico; Quattrone, Andrea; Caracciolo, Manuela; Sabatini, Umberto; Cherubini, Andrea; Quattrone, Aldo
Abstract: Introduction: The aim of this study was to investigate the thalamic biochemical profile in patients with essential tremor (ET), using proton magnetic resonance spectroscopy ( 1 H-MRS), and to explore the correlations between clinical and biochemical data. Methods: Sixteen patients with ET and 14 healthy controls participated in this study. After conventional MR imaging, single-voxel 1 H-MRS (TR = 2000 ms; TE = 28 ms) was performed by using a PROBE-SV system implemented on a 3-T scanner. A voxel of 10 × 10 × 15 mm involving the ventrointermediate (Vim) nucleus was acquired in each thalamus of all subjects. Peak areas of N-acetyl-aspartate + N-acetyl-aspartyl-glutamate (NAA), creatine + phosphocreatine (Cr), glycerophosphocholine + phosphocholine (Cho), and glutamate + glutamine (Glx) were calculated using a version 6.3-1 K of the fitting program LCModel for each voxel. Comparative and correlation analyses were performed on the NAA, Cr, Cho, and Glx concentrations, as well as on the values of the NAA/Cr, a neural density marker, Cho/Cr, a membrane marker, and Glx/Cr, an intracellular neurotransmitter marker. Results: Patients with ET showed a significant increase in Glx concentration and Glx/Cr ratio values in both thalami, compared to healthy controls, whereas no difference inter-group was found for the other metabolites and NAA/Cr and Cho/Cr ratio values. Of note, the tremor severity was positively related to increased Glx concentrations and Glx/Cr ratio values in ET group. Conclusions: Our study shows that 1 H-MRS can highlight in vivo metabolic abnormalities in the thalami of ET patients, supporting the evidence that the increase of thalamic glutamatergic transmission can play a role in developing of tremor in ET. Highlights: 1 H-MRS is able to detect in vivo neurometabolic alterations in brain tissue. We found increased glutamate + glutamine levels in thalamus ET patients. Increased thalamic glutamatergic transmission plays a role in ET tremor.